A Lagrangian study of the Antarctic polar vortex. - PAPARELLA, Francesco; A. Babiano; C. Basdevant; A. Provenzale; P. Tanga (Journal of Geophysical Research: Atmospheres, 1997)
We study the dynamics of passively advected tracers in the Antarctic polar vortex, using the wind fields provided by the European Centre for Medium-Range Weather Forecasts' (ECMWF) analysis from August to October 1993. Advection on both isopycnal (0.0938 kg/m^3) and isentropic surfaces (470 K) is considered. A new definition of the vortex edge, identified as the maximum of the kinetic energy is compared with the definition based on the maximum gradient of Ertel potential vorticity. Using the kinetic energy criterion, we study the permeability of the polar vortex in the framework of the launch strategy of the Stratospheric Eole (Strateole) polar ozone experiment. We compare the dynamics of balloons launched from the latitudes corresponding to three different possible launching sites for the Strateole experiment, and we provide a quantitative estimate of the probability that a passive tracer may cross the vortex edge, confirming the strong impermeability of the polar vortex to inward and outward particle motion.